Systematic comparison of bacterial feeding strains for increased yield of Caenorhabditis elegans males by RNA interference‐induced non‐disjunction. Issue 18 (24th July 2014) - Timmons, Lisa; Luna, Hayley; Martinez, Jordan; Moore, Zachary; Nagarajan, Vaishnavi; Kemege, Juliana Metichecchia; Asad, Nadeem
Abstract : Rare Caenorhabditis elegans males arise when sex chromosome non‐disjunction occurs during meiosis in self‐fertilizing hermaphrodites. Non‐disjunction is a relatively rare event, and males are typically observed at a frequency of less than one in five hundred wild‐type animals. Males are required for genetic crosses and phenotypic analysis, yet current methods to generate large numbers of males can be cumbersome. Here, we identify RNAi reagents (dsRNA‐expressing bacteria) with improved effectiveness for eliciting males. Specifically, we used RNAi to systematically reduce the expression of over two hundred genes with meiotic chromosome segregation functions, and we identified a set of RNAi reagents that robustly and reproducibly elicited male progeny. Abstract : dsRNA‐expressing bacterial strains were assessed for effectiveness in eliciting X‐chromosome disjunction and C. elegans males. Bacterial strains were identified and new dsRNA‐expressing plasmids were generated that improve the yield of males. Sterility defects observed in some Him mutant males can be overcome by using RNAi to elicit mutant males.